Association between immigration enforcement encounters and COVID-19 testing and delays in care: a cross-sectional study of undocumented young adult immigrants in california - May Sudhinaraset; Hye Young Choi; Ezinne Nwankwo; Maria-Elena De Trinidad Young (BMC Public Health, 2022)
Abstract Background Undocumented immigrants are expected to face increased risks related to COVID-19 due to marginalizing restrictive immigration policies. However, few studies have assessed the prevalence of direct encounters with the immigration enforcement system among the undocumented and its impacts on their COVID-related health behaviors and outcomes. In this study, we quantify undocumented immigrants' lifetime exposure to various immigration enforcement tactics and their association with delays in COVID-19 testing and healthcare behaviors. Methods This cross-sectional study included a non-random sample of 326 Asian and Latinx undocumented immigrants in California from September 2020 to February 2021. The primary exposure was immigration enforcement encounter scores ranging from 0–9, assessed through self-reports of direct experiences with the immigration system, immigration officials, and law enforcement. The main outcomes were positive test for COVID-19, had or suspected having COVID-19, and delayed or avoided testing and/or treatment for COVID-19 due to immigration status. We used multivariable logistic regression models to examine the association between the primary exposure and outcomes of interest. Results Among 326 participants, 7% had received a positive COVID-19 test result, while 43% reported having or suspected having COVID-19. Almost 13% delayed or avoided COVID-19 testing and/or treatment because of their immigration status. Overall, an increase in immigration enforcement encounters was associated with higher odds of suspecting having had COVID-19 (aOR = 1.13; 95% CI: 1.01,1.26). Reporting an additional enforcement encounter was associated with higher odds of delaying or avoiding testing and/or treatment because of immigration status (aOR = 1.53, 95% CI: 1.26,1.86). Compared to their Latino counterparts, Asian respondents were more likely to report higher odds of delaying or avoiding testing and/or treatment (aOR = 3.13, 95% CI: 1.17,8.42). There were no significant associations between the enforcement score and testing positive for COVID-19. Additionally, while Latinxs were more likely to report immigration enforcement encounters than Asians, there were no differences in the effects of race on COVID-19 testing and healthcare behaviors in models with race as an interaction term (p < 0.05). Conclusions Immigration enforcement encounters compound barriers to COVID-19 testing and treatment for undocumented immigrants.